The hooligans [compact disc, unabridged] - Deutermann, P. T., (Peter T.), 1941- (Brilliance Audio, 2020)
Loosely-organized in fast moving squadrons, PT (patrol torpedo) boats were the pesky nemesis of the formidable Japanese navy, dubbed 'the mosquito fleet' and 'devil boats' for their daring raids against warships, tankers, and transport ships. After the Pearl Harbor raid plunges America into war, young surgical resident Lincoln Anderson enlists in the Navy medical corps. His first deployment comes in August 1942 at Guadalcanal, when after a brutal sea battle and the landing of Marines on the island, Anderson finds himself triaging hundreds of casualties under relentless Japanese air and land attacks. But with the navy short of doctors, soon Anderson is transferred to serve aboard a PT boat.